Marital Strain Exacerbates Health Risks of Filial Caregiving: Evidence from the 2005 National Survey of Midlife in the U.S - Kang, SunWoo (J Fam Issues, 2014)
This study examined linkages between providing care for a parent (in contrast to not providing any care to other kin or nonkin) and four dimensions of physical health (self-rated health, functional limitations, physical symptoms, chronic conditions), as well as moderation of these linkages by gender and a negative dimension of marital quality--marital strain. Regression models were estimated using telephone and self-administered questionnaire data from 1080 married men and women who participated in the National Survey of Midlife in the U.S. (MIDUS) 2005. Although providing filial care was not found to be a global health risk for all married caregivers, marital strain was a critical factor in determining risk. Contrary to hypothesis, robust gender differences were not in evidence. But among both women and men, caregiving for a parent in the presence of high levels of marital strain was associated with significantly poorer health across all four evaluated outcomes.